Direct Democracy During Martial Law: Ways to Realize the People’s Right to Power - Mykhailov, Mykhailo (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The article is devoted to the analysis of the problem of realization of democracy in the conditions of martial law. It has been established that direct democracy is an important element in the implementation of the principle of people’s sovereignty. This principle is not limited. Protection of people’s sovereignty is an important component of the state’s defense function. It was established that the restriction of human and civil rights, as well as the redistribution of powers between public authorities and local governments, aimed at ensuring defense capability and bringing victory closer. Not all current issues that need to involve citizens are related to solving such problems. Therefore, the author concludes that the limited use of direct democracy during martial law is quite appropriate. The author substantiates the need for a moderate approach to restricting the right of citizens to directly exercise power. The search for possible forms and manifestations of direct democracy, which could ensure the implementation of the real will of citizens, regardless of the martial law. The author considers the institution of direct electronic democracy to be the most successful for this. Its implementation is possible at least at the local level in the regions, where it is possible to ensure the verification of citizens and further rule-making process by the representative authorities. It is proposed to start comprehensive work on studying the possibility of creating blockchain platforms for direct e-democracy.